A history of the South African police in Port Elizabeth, 1913-1956 - Watson, Kelvin Innes (Rhodes University, Faculty of Humanities, Department of History, 2000)
This thesis investigates the policing activities of the South African Police (SAP) in Port Elizabeth from the formation of the SAP in 1913 to the creation of two separate police districts in the city in 1956. It begins with the recruitment and training of police personnel, outlining the difficulty in obtaining sufficient white recruits for most of the period while at the same time stressing the ease with which the Force was able to obtain black recruits. The preponderance of Afrikaner policemen serving in Port Elizabeth from the 1920s onwards is made clear, as is the para-military nature of the SAP, which was maintained and reinforced as a result of training methods and the process of socialisation. As state servants, police personnel were expected to serve loyally and obediently a state becoming increasingly repressive towards its black citizens. Generally inadequate conditions of service remained the norm throughout the period yet the SAP's commitment to the state never wavered, bar one isolated, short-lived incidence. The administration and functioning of policing in Port Elizabeth is explored by focussing on specific organisational features pertinent to the city and the changes wrought by the police hierarchy to deal with the city's demographic and spatial expansion. The SAP tended to employ three different forms of policing in the city as a result of its apartheid-driven agenda which compelled it to differentiate between the various population groups in terms of maintaining law and order. The privileged white community experienced routine, civil policing whereas the black community was policed largely in a socially and politically oppressive manner; this was in line with government policy. On the whole, however, the more brutal and sinister nature of policing was yet to come to the fore although this thesis does point towards the increasingly repressive nature of policing in South Africa during the apartheid era.
Keywords: Police -- South Africa -- Eastern Cape -- South African; Police -- South Africa -- Port Elizabeth -- History; Police -- South Africa -- Port Elizabeth -- History